Research on High-Temperature Resistance of Iron Tailings Concrete - Tian, Shibo; Chen, Juannong (Scientific Journal of Technology, 2025)
Iron tailings, as industrial solid waste generated during the mineral processing operations, are experiencing a continuous increase in their reserves due to ongoing mining activities. The massive accumulation of iron tailings not only occupies valuable land resources but also causes severe ecological damage to mining areas. The utilization of solid waste materials for the production of recycled aggregate concrete is of crucial importance for the sustainable development of the construction industry. In recent years, research on solid waste-based concrete, particularly focusing on the durability and high-temperature resistance of iron tailings concrete, has advanced rapidly, yielding a series of notable achievements. This paper analyzes multiple articles on iron tailings concrete research, summarizing the existing outcomes and identifying the gaps in the current knowledge base. The objective is to provide a reference for future research endeavors in this domain.